Tree surgery: A boon for damaged tree species - Singh, Lokendra; Singh, Mam Chand; Amala, Ediga; Arzoo, Eram (Indian Horticulture, 2025)
This article highlights the importance of tree surgery, particularly in preserving large and heritage trees that are over 100 years old. Tree surgery plays a crucial role in saving trees that are at risk of falling due to trunk hollowness. When a tree trunk becomes hollow, the likelihood of the tree collapsing increases significantly. If such a tree is located near a road or national highway, it can pose a serious hazard. Additionally, replacing a damaged tree requires considerable time and financial resources. Therefore, tree surgery is a valuable solution for restoring damaged trees and reducing the risk of tree falls.